Unmet Needs in Dystonia - Alberto Albanese (Frontiers Research Topics, 2017)
This Research Topic contains proceedings of the final conference for COST Action BM1101 "Network of dystonia syndromes". The topic highlights consolidated knowledge and unmet needs in a field that is evolving very fast. This publication is based upon work from COST Action BM1101, supported by COST (European Cooperation in Science and Technology).